Traduire les médias dans une communauté de pratique virtuelle : Expérience du portail francophone le Courrier des Balkans - Translating media in a virtual community of practice: The experience of the French-language news portal Le Courrier des Balkans - Jasmina Tatar Andelic (JoSTrans: The Journal of Specialised Translation)
This article analyses the translation practices and professional development of translators at Le Courrier des Balkans, a French-language news portal serving the Balkans, founded in 1998. The article begins by establishing that Le Courrier des Balkans corresponds to an online community of practice, offering its members a contextualized learning environment. It reports on findings from a questionnaire administered to members, which asked them to reflect on their contribution to the community of practice, on the evolution of their approach to translation and on their professional development. Findings from the research establish the significance of the issue of ethics to the translation practices of this community. This is explained, in part, by the fact that some community members are activists in their respective countries and take strongly activist positions, particularly in times of conflict. Findings from this research also indicate that members value this community of practice for the opportunities for professional development that it affords and the access to terminological and textual resources that it provides.